2008
DOI: 10.1097/tp.0b013e318181e02d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prophylactic Splenic Artery Modulation on Portal Overperfusion and Liver Regeneration in Small-for-Size Graft

Abstract: In SFS graft with severe portal hypertension, prophylactic splenic embolization/ligation seems to relieve portal overperfusion injury and contributes in improvement of posttransplantation prognosis through liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 42 publications
1
86
0
Order By: Relevance
“…Although portal inflow modulation has been reported to prevent SFSS, (33)(34)(35)(36) the role of modulation remains controversial. (37,38) We previously reported that small graft size is associated with high PVP and that high PVP (25 mm Hg) is correlated with posttransplant thrombocytopenia, (39) but we have not performed any portal inflow modulation because there has not been a recipient with high PVP since that study.…”
Section: Discussionmentioning
confidence: 99%
“…Although portal inflow modulation has been reported to prevent SFSS, (33)(34)(35)(36) the role of modulation remains controversial. (37,38) We previously reported that small graft size is associated with high PVP and that high PVP (25 mm Hg) is correlated with posttransplant thrombocytopenia, (39) but we have not performed any portal inflow modulation because there has not been a recipient with high PVP since that study.…”
Section: Discussionmentioning
confidence: 99%
“…23,33,35 This modulation may be done by performing splenectomy, splenic artery ligation, or hemiportocaval shunt. [35][36][37][38][39][40][41][42][43] The frequency of portal flow modulation was similar with left and right lobe grafts. The mean baseline portal vein flow was greater with left than right lobes (Table 2).…”
Section: Discussionmentioning
confidence: 69%
“…However, an exaggerated HABR may contribute to ischemic injury in states of portal hyperfusion, as seen in small for size grafts [48,49] . Prophylactic splenic artery modulation [50,51] produced a significant reduction in portal flow causing a significant reduction in incidence of SFSS.…”
Section: Intraoperative Featuresmentioning
confidence: 99%